Association between hypertension and hearing loss: a systemic review and meta-analysis - Xiaohua Jin; Xiaohua Jin; Xianpeng Xu; Xianpeng Xu; Jingjing Wang; Jingjing Wang; Xinghong Liu; Xinghong Liu; Xinxing Deng; Xinxing Deng; Hui Xie; Hui Xie (Frontiers in Neurology)
ObjectiveTo systematically evaluate the association between hypertension and hearing loss.MethodsA standardized search for studies on hypertension and hearing loss in PubMed, Embase, Scopus, and Web of Science was performed using subject terms, free terms, and keyword combinations for the period of library construction to March 2024. Meta-analysis was performed using RevMan 5.4 and STATA 18.0.ResultsA total of 12 studies were included, assessing 594,676 participants. The combined OR using the random effects model was 1.849 (95% CI: 1.549, 2.208). Heterogeneity in this analysis was high (I2 = 98%, p < 0.1), and by sensitivity analysis we found that the heterogeneity may have originated from 3 studies, the removal of which significantly reduced the heterogeneity and had a small effect on the effect size [OR (95%CI): 1.893 (1.834, 1.953), I2 = 0.0%, p = 0.465].ConclusionHypertension may be one of the risk factors for hearing loss. Identification of hypertension can help in early assessment and management of hearing loss risk.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023460001.